Pemberdayaan Kader Posyandu Dalam Deteksi Dini Dan Pencegahan Stunting Di Desa Kubang Jaya - Neni Ristiani; Sabrina Hayati; Nadya Putri Auliya (jurnal ABDIMAS Indonesia, 2024)
Stunting is a public health problem that is often found, especially in developing countries. The high incidence of stunting in children will affect children's growth, development and intelligence in the future. Overcoming stunting incidents can be done through prevention and early detection. Stunting prevention can be implemented before the baby is born, namely by providing food with adequate nutrition to pregnant women. Early detection is important so that the problem of stunting can be resolved immediately. The aim of this community service is to increase the role of posyandu cadres in preventing stunting by increasing cadres' knowledge about stunting, prevention and the importance of early detection. After this program is carried out, it is hoped that posyandu cadres can play an active role in monitoring pregnant women and toddlers in their environment as an effort to prevent and early detect stunting incidents.